Climate change impact assessment under data scarcity by hydrological and hydrodynamic modeling in Izmit Bay/Turkey - Onkal Engin, Guleda; Adiller, Ahmet; Klug, Philipp; Celen, Meltem; Herrmann, Frank; Bach, Heike; Wendland, Frank (Yildiz Technical University, 2021)
To assess climate change impact on the hydrology of Izmit Bay, a coupled model chain using the results of four combinations of Global Climate Models (GCMs) and Regional Climate Models (RCMs) and consisting two hydrological models (mGROWA and PROMET) and one hydrodynamic model (MIKE 3HD) was established. Climate model data of the 4 GCM-RCM combinations were applied to both hydrological models. The resulting 8 streamflow data of the hydrological models were then applied to the MIKE 3HD to assess possible hydrodynamic situations in Izmit Bay. Related model results indicate a range of possible future streamflow regimes suitable for the analysis of climate change impact on Izmit Bay. In order to evaluate the effects of the hydrological changes only on the bay, the bay was considered as closed in terms of hydrodynamics. There is a clear indication that the climate change induced impacts on streamflow may influence the sea level in the Bay to a minor extent. However, climate change induced water exchange processes in the Bay may have a much bigger influence. Hence, it is suggested that further simulations should be run once the hydrologic regime of the Marmara Sea has been assessed in a broader macro-scale study. © 2022 Elsevier B.V., All rights reserved.
Keywords: m-GROWA; MIKE 3HD; PROMET; River discharge